Evaluating Community Participation in the Public Policy Formulation Process in Indonesia - Ambo Masse; Abdul Sahid Ilyas (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
This study aims to analyze the extent to which community participation influences the public policy-making process in Indonesia. The public policy-making process encompasses a series of actions and decisions that lead to the development and adoption of specific public policies. Community participation is a critical element in this process as it aids in shaping, defining, and implementing policies that directly affect the community. This research employs a qualitative methodology, gathering data through in-depth interviews, document studies, and participant observations of stakeholders directly involved in the public policy formulation process. The findings indicate that while community participation is granted a significant role in policy formulation, several barriers remain, such as a lack of information, limited technical capacity among community members, and other structural issues that impact the level and quality of participation. This study advocates for increased transparency and openness of information, training and capacity-building initiatives for communities, and enhanced participation in the policy formulation process. It contributes to the literature on the role and influence of community participation in public policy formulation, particularly in the Indonesian context.